Rotational alignment effects in NO(X) + Ar inelastic collisions: an experimental study - Brouard, M; Chadwick, H; Eyles, C J; Hornung, B; Nichols, B; Aoiz, F J; Jambrina, P G; Stolte, S (The Journal of chemical physics, 2013)
Rotational angular momentum alignment effects in the rotationally inelastic collisions of NO(X) with Ar have been investigated at a collision energy of 66 meV by means of hexapole electric field initial state selection coupled with velocity-map ion imaging final state detection. The fully quantum state resolved second rank renormalized polarization dependent differential cross sections determined experimentally are reported for a selection of spin-orbit conserving and changing transitions for the first time. The results are compared with the findings of previous theoretical investigations, and in particular with the results of exact quantum mechanical scattering calculations. The agreement between experiment and theory is generally found to be good throughout the entire scattering angle range. The results reveal that the hard shell nature of the interaction potential is predominantly responsible for the rotational alignment of the NO(X) upon collision with Ar.